Wolfsburg: Stadtneugründung und Spiegel der Stadtideen des 20. Jahrhunderts: Eine Stadt entwächst den Kinderschuhen. Issue 1 (2nd January 2016) - Froberg, Nicole; Hirschheide, Kai-Uwe
Abstract : Wolfsburg is the auto city of Europe – a city that was planned and built for the newly established Volkswagen factory from 1 July 1938 on and, as regards its evolution, is still closely associated with the global company to this day. This comparably small Lower Saxony city, which grew from practically nothing to its current population of 125 000 in-habitants, tells of the relationships between politics, society, economy and urban planning like almost nowhere else. From a historical perspective, Wolfsburg is regarded as the founding of a National Socialist city, however in terms of its urban planning principles and its prominent architectural features it may be viewed as perhaps the most important late-modernist city in Europe. Initially founded on a plot with just 1000 inhabitants, Wolfsburg was created as a ' functional city', as laid down in the Athens Charter, and later developed according to the then influential ideal of the 'car-friendly city'. Almost 80 years later and these concepts of urban planning in the 20th century are under scrutiny and being stretched to their limits. Yet Wolfsburg, still in its infancy, today remains a 'city lab', continuing to break the mould through its many pilot projects.